At home afloat : women on the waters of the Pacific Northwest - Pagh, Nancy, 1963- (University of Calgary Press ; University of Idaho Press, 2001)
Women were considered bad luck on boats at sea until far into the nineteenth century. Nancy Pagh studies women active in the Pacific maritime off the Northwest and Canadian coasts as these traditional prohibitions broke down. She examines the influence of gender on the roles of women at sea, the spaces they occupy on boats, and the language they use to describe their experiences, natural surroundings, and contact with native peoples.